(untitled) (Rajarshi Janak University Research Journal, 2025)
Life insurance is an agreement where the insurer provides a lump-sum payment to beneficiaries in return for regular premiums. Its scope covers not only risk protection but also savings, investments, financial security, and tax benefits. The main objective of the study was to explore the barriers and perceptions behind life insurance avoidance in Nepal. This study focuses on exploring and analyzing the determinants influencing life insurance purchasing decisions in Nepal. It particularly examines customers’ perceptions toward life insurance policies and identifies the major barriers that discourage individuals from purchasing such policies. A descriptive design is employed for this research, utilizing appropriate tables to analyze and present the data. The analysis focuses on current and prospective customers as a population. To achieve objectives of the study, only primary data were gathered using judgmental sampling, in which chosen respondents filled out questionnaires. The data analysis showed that most customers of life insurance companies in Nepal are dissatisfied with several factors including marketing strategies, policy, service, returns after maturity, and their overall trust in insurance. Many respondents (69.68 % policyholder) compared life insurance with cooperatives and finance companies, often viewing it as a fraudulent and few (28.36% having no insurance policies) responded as the benefits would only be paid after death. Additionally, the findings indicated that majority of customers bought life insurance policies not because they were personally interested, but mainly due to the constant pressure from agents and staff working in the sector. These findings suggest that lack of trust and awareness are the main barriers to adopting life insurance in Nepal, rather than financial status.